A review on the pharmacology, pharmacokinetics and toxicity of sophocarpine - Wei, Shichao; Xiao, Junshen; Ju, Feng; Liu, Jin; Hu, Zhaoyang (Frontiers in Pharmacology, 2024)
Sophocarpine is a natural compound that belongs to the quinolizidine alkaloid family, and has a long history of use and widespread distribution in traditional Chinese herbal medicines such as Sophora alopecuroides L., Sophora flavescens Ait., and Sophora subprostrata This article aims to summarize the pharmacology, pharmacokinetics, and toxicity of sophocarpine, evaluate its potential pharmacological effects in various diseases, and propose the necessity for further research and evaluation to promote its clinical application. A large number of studies have shown that it has anti-inflammatory, analgesic, antiviral, antiparasitic, anticancer, endocrine regulatory, and organ-protective effects as it modulates various signaling pathways, such as the NF-κB, MAPK, PI3K/AKT, and AMPK pathways. The distribution of sophocarpine in the body conforms to a two-compartment model, and sophocarpine can be detected in various tissues with a relatively short half-life. Although the pharmacological effects of sophocarpine have been confirmed, toxicity and safety assessments and reports on molecular mechanisms of its pharmacological actions have been limited. Given its significant pharmacological effects and potential clinical value, further research and evaluation are needed to promote the clinical application of sophocarpine.